Evrim Bougie: A new instrument in the management of urethral strictures - Yilmaz, Ugur (BioMed Central, 2001)
BACKGROUND: In this study a new instrument and technique is described for the endoscopic treatment of complete posterior urethral strictures, which may result in serious complications and sometimes require troublesome treatments. METHODS: Three patients with complete posterior urethral obstruction were treated endoscopically with the guidance of a new instrument: Evrim Bougie. Evrim Bougie looks like a Guyon Bougie, has a curved end, which facilitates getting into the bladder through the cystostomy tract and with a built in channel of 1.5 mm in diameter for a sliding needle exiting at its tip. Having confirmed fluoroscopically and endoscopically that the sliding needle had passed across the strictured segment, the strictured segment was incised with internal urethrotomy, distal to the strictured segment, and urethral continuity was accomplished. At the end of the operation a Foley urethral catheter was easily placed into the bladder per urethra. Patients were instructed in self-catheterization after removal of the urethral catheter. All patients achieved normal voiding at postoperative 7th month follow-up evaluation. CONCLUSION: Internal urethrotomy could be performed under the guidance of the sliding needle of Evrim Bougie advanced from above the posterior urethral strictures, which to our knowledge was described for the first time in the English literature. We also believe that there may be other possible indications of Evrim Bougie for different procedures in urethral surgery.